2021
DOI: 10.1002/hed.26816
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of oral cancer screening approaches by visual examination: Systematic review

Abstract: The present study is the first systematic review of papers that have performed a full economic evaluation on oral cancer screening strategies using visual oral examination. The review questions were (1) Is screening a cost-effective strategy in oral cancer? (2) What is the most cost-effective strategy among the different screening approaches in oral cancer? The main outcome measure was the incremental cost-effectiveness ratio. The study identifies and reviews seven full economic evaluations. The included studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
10
0
2
Order By: Relevance
“…Finally, a successful targeted screening program depends on the accurate identification of a high-risk population, which can be costly and sometimes challenging. To our knowledge, these nuances of targeted screening have not been thoroughly examined in the economic evaluation literature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a successful targeted screening program depends on the accurate identification of a high-risk population, which can be costly and sometimes challenging. To our knowledge, these nuances of targeted screening have not been thoroughly examined in the economic evaluation literature …”
Section: Discussionmentioning
confidence: 99%
“…If multiple reports belonged to the same study, we included them all if they presented data at different stages of that study. We did not consider cost-effectiveness studies since those articles had already been reviewed . We also excluded proof-of-concept studies or diagnostic accuracy assessments .…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the total number of studies on screening programs for oral cancer was rather small compared to other types of cancer, such as prostate and breast cancer [ 24 , 25 ]. Furthermore, from 2021 to 2023, no new studies were reported based on a recent review of oral cancer screening approaches and a literature summary [ 26 , 27 ]. This reflected the fact that although many oral cancer screening programs were recommended and instituted at various levels, they were often not evaluated rigorously in terms of their economic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Early diagnosis and clinically implemented oral cancer screening have been evidenced to provide suitable relief to both medical systems and patients alike as a beneficial and cost-effective strategy, although further research is required in this regard. [13] Currently, evidence supports that education of the population facilitates improved understanding of the disease and its associated risks in addition to highlighting wellknown risk factors, and all of which can aid in the prevention of oral cancer development. [14] These functional approaches also provide an opportunity to decrease the burden of cost for oral cancer care and treatment with regard to both direct and indirect costs.…”
Section: Introductionmentioning
confidence: 99%